Riding on Digital Transformation to increase the Women and Youth employment in the post-COVID-19 Era – A Study on Zimbabwe - Garikayi Emmanuel Gondo; Prof. Lorna B. Holtman; Prof. Ravinder Rena; Dr. Colleen Gail Moodley (Researchers World - International Refereed Social Sciences Journal, 2023)
Purpose: The main purpose of this paper is to shed a light on the employment-to-population ratio of women in Africa continues to trail behind men, despite a gradual increase in their participation in the paid labour force. This discrepancy can be attributed to historical factors during previous industrial revolutions, where women were excluded from the labour force due to the focus on labour-intensive mass production, and their prioritization of family commitments. However, with the rise of technology and cyber-physical systems in subsequent industrial revolutions, more women have started engaging in paid employment. The work-from-home concept, highlighted during the Covid-19 pandemic, showcased the feasibility of remote work arrangements, providing an opportunity for African policymakers to empower women and youth by revisiting their policies. Methodology: This study was conducted on this context to discover a practical knowledge on the digital transformation of the women and youth with a major focus on the Zimbabwean context. To achieve this objective, an empirical review of previous works of literature on digital transformation and work from home was conducted. The study based on the thematic analysis of the data obtained from literature review. To support our research objectives, we conducted a thorough literature search using thematic analysis and developed a skills framework. Implications: Exploring the work-from-home concept, we aim to provide a comprehensive framework outlining the necessary skills for the upcoming fifth industrial revolution, which demands a workforce capable of effectively interacting with technological devices. Originality: This paper contributes as an intellectual hub; universities can use the framework to design courses empowering marginalized groups, especially women, aligning with national policies for inclusive economic growth and societal development in a post-Covid-19 world.